2020
DOI: 10.4103/jfmpc.jfmpc_164_20
|View full text |Cite
|
Sign up to set email alerts
|

Infant and young child feeding practices among mothers of children aged 6 months -2 years in a rural area of Haryana: A qualitative study

Abstract: Background: India, a low-middle income and a developing country is combating with a triple burden of malnutrition with a very cost-effective measure, infant and young child feeding (IYCF) practices. But there are a lot of challenges in its implementation which need to be catered. The objective of the present qualitative study was to assess IYCF practices among mothers of children aged 6 months to 2 years in a rural area of Haryana. Method: Qualitative study was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Mothers of children aged under five years are required to be well informed about the significance of exclusive breastfeeding, and the nutritional value of the complementary food. Best infant and young child feeding (IYCF) practices are essential to minimize the morbidity and mortality rates among neonates and children as suggested by the WHO [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers of children aged under five years are required to be well informed about the significance of exclusive breastfeeding, and the nutritional value of the complementary food. Best infant and young child feeding (IYCF) practices are essential to minimize the morbidity and mortality rates among neonates and children as suggested by the WHO [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Kamble et al . [ 3 ] among mothers on IYCF showed that working mothers are unable to follow IYCF practices completely. There was a paucity of knowledge regarding complimentary food and feeding frequency among mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inadequate, inappropriate complementary feeding, or unhygienic practices lead to recurrent and persistent infections and malnutrition that ends in growth retardation, immunodeficiency, and eventually fatal outcomes. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies also revealed that pre-lacteal feeding rituals were major barriers to exclusive breastfeeding. For example, pre-lacteal feeding rituals (like jaggery, honey, sugar water, cow milk, and ghee) were observed in many previous studies [27,47,[50][51][52]60]. A 25-year-old woman expressed the cultural belief for feeding honey to a newborn child as:…”
Section: Social and Cultural Barriersmentioning
confidence: 99%
“…Consequently, home delivery or using a traditional birth attendant (TBA) who was receptive to herbs became a preferred choice [1,57]. Many studies revealed that the culture of discarding rst milk (colostrum) was a major barrier to exclusive breastfeeding and newborn health [24,27,47,50,51,62]. In the tribal community in Kalahandi district, Odisha, India, one traditional midwife explained that:…”
Section: Social and Cultural Barriersmentioning
confidence: 99%